Asymptotically Stable Single‐Legged Passive Dynamic Hopping. Issue 8 (13th April 2022) - Nagase, Jun‐ya; Yang, Sungna; Satoh, Toshiyuki; Saga, Norihiko
Abstract : Passive dynamic locomotion arises only as a result of dynamic interaction with the ground, that is, without actuators, sensors, or controls. For exploring the principles of human and animal locomotion, passive dynamics is important. One important characteristic is the existence of a stable limit cycle in passive locomotion dynamics. However, to date, no limit cycle has been found in passive dynamic hopping (PDH). Numerical simulation reveals that the leg dynamics of PDH has a stable limit cycle. © 2022 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.